2020
DOI: 10.5812/ijpbs.100281
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder in Emergency Medical Services Personnel in Iran: A Letter to the Editor

Abstract: Post-traumatic stress disorder (PTSD) is a complex physical, cognitive, emotional, behavioral, and psychological disorder that occurs as a result of an accident or life-threatening incident. It is related to disturbing thoughts, anxiety, sleep disturbance, and avoidance of a traumatic event that ultimately leads to social, occupational and interpersonal disorders (1-3). Emergency Medical Services personnel experience workplace events that are direct threats to their well-being; they are also faced with events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Also, the findings of another meta-analysis study indicated a 14.2% PTSD prevalence among police forces [ 33 ]. Based on the meta-analysis study conducted by Golitaleb et al, a prevalence of 50.21% was obtained for PTSD among EMS personnel [ 34 ]. Another meta-analysis study by Sahebi et al revealed a PTSD prevalence of 13.52% in health care professionals during the Covid-19 pandemic [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings of another meta-analysis study indicated a 14.2% PTSD prevalence among police forces [ 33 ]. Based on the meta-analysis study conducted by Golitaleb et al, a prevalence of 50.21% was obtained for PTSD among EMS personnel [ 34 ]. Another meta-analysis study by Sahebi et al revealed a PTSD prevalence of 13.52% in health care professionals during the Covid-19 pandemic [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a review study by Sahebi et al [37] in 2020 showed that the prevalence of PTSD was 23.17% among Iranian firefighter. Another study by Golitaleb et al [38] revealed that the prevalence of PTSD was 50.20% among pre-hospital emergency personne. Klimley et al [40] also stated that more than 80% of first responders (police, firefighters, and EMS personnel) had experienced occupational traumatic incidents, and the prevalence of PTSD was estimated as 10-15% among them [39][40][41].…”
Section: Discussionmentioning
confidence: 95%
“…Within the last years, many societies were exposed to multiple stressors and crises such as the COVID-19 pandemic, economic crises, wars and armed conflicts, or natural disasters 1 . As stress is among the leading causes for the onset and persistence of mental disorders, those societal challenges put the mental health of substantial parts of the population at risk, resulting in a serious public mental health issue [2][3][4][5] . This poses the question of how people can maintain or regain their mental health in face of societal challenges -that is, how people can respond resiliently.…”
Section: Introductionmentioning
confidence: 99%